2016
DOI: 10.1002/ldr.2610
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Heterogeneity of Soil Available Nitrogen During Crop Growth Stages on Mollisol Slopes of Northeast China

Abstract: Spatiotemporal heterogeneity of soil available nitrogen (AN) (sum of NO3−–N and NH4+–N) is the essential basis for soil management and highly correlates to crop yield. Both geostatistical and traditional analyses were used to describe the spatiotemporal distribution of AN in the 0–20‐cm soil depth on typical Mollisol slopes (S1 and S2) in Northeast China. The concentration of NO3−–N dynamics at slope positions was typically opposite to NH4+–N. The peak values of AN typically moved from the summit of the slope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 44 publications
0
8
1
Order By: Relevance
“…We also found that there are significant correlations between most indices of chemical properties, indicating that significant interactions exist in soil properties which may degrade or develop together. In general, spatial heterogeneity of soil nutrients could be induced by slope position due to physical movement of the soil from higher slope position to lower slope position (Noorbakhsh et al, 2008;Zhang et al, 2016). However, our study showed that slope positions did not significantly affect soil chemical properties and stoichiometric ratios except C: N ratio (Table 2).…”
Section: Discussioncontrasting
confidence: 76%
“…We also found that there are significant correlations between most indices of chemical properties, indicating that significant interactions exist in soil properties which may degrade or develop together. In general, spatial heterogeneity of soil nutrients could be induced by slope position due to physical movement of the soil from higher slope position to lower slope position (Noorbakhsh et al, 2008;Zhang et al, 2016). However, our study showed that slope positions did not significantly affect soil chemical properties and stoichiometric ratios except C: N ratio (Table 2).…”
Section: Discussioncontrasting
confidence: 76%
“…However, in our study, SM in the SA treatment was consistently higher at the back of the slope and lower at the bottom of the slope, while not consistently higher at the top. This may also be influenced by crop growth, landscape, and vigorous crop growth, which significantly decreased or increased soil water levels [25]. In this study, straw amendment increased crop yield at the top and the back of the slope with relatively low SM, but decreased crop yield at the bottom.…”
Section: Discussionmentioning
confidence: 60%
“…We aim to determine how SA changes soil physicochemical properties and influences crop growth and yield in the Mollisol region of Northeast China. The information from the results of the impacts of straw amendment on crop yield can be used for the development of local residue management and can also be transferred to other Mollisol regions, such as the mid-latitudes of North America, Eurasia, and South America with larger Mollisol areas [25]. (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…A pot experiment was used in this study, and soils were taken from the farmland of the Harbin region in Heilongjiang Province of Northeast China (no history of plastics application). The soil was classified as typical black soil according to the Chinese Soil Classification (CST) and Mollisols in the United States Soil Classification (USST) ( Zhang et al, 2017 ). The basic physicochemical properties of soil are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%